2018
DOI: 10.1007/s00784-018-2562-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of orofacial profiles in 5- and 10-year-old Swedish children with and without cleft lip and/or palate

Abstract: Impaired orofacial function seen in children with CL/P can be one of many risk factors for caries development, and it is suggested to be a part of caries risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
2
0
3
Order By: Relevance
“…These children require long-term multidisciplinary care. Dental decay, hypoplasia, malocclusion, and gingivitis are the common dental health issues they face (Dahllof et al, 1989, Harris et al, 2004; Sundell and Marcusson, 2019). A recently conducted systematic review and meta-analysis found that “individuals with cleft lip and/or palate have higher caries prevalence, both in the deciduous and the permanent dentitions” (Worth et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These children require long-term multidisciplinary care. Dental decay, hypoplasia, malocclusion, and gingivitis are the common dental health issues they face (Dahllof et al, 1989, Harris et al, 2004; Sundell and Marcusson, 2019). A recently conducted systematic review and meta-analysis found that “individuals with cleft lip and/or palate have higher caries prevalence, both in the deciduous and the permanent dentitions” (Worth et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is fully in line with a systematic review which reported that eating, speaking and emotional well-being are the most influenced dimensions of OHRQoL among children and adolescents with CLP (Queiroz Herkrath et al 2015 ). The reason for the impact on eating may be restricted orofacial function among the study participants as suggested by Sundell and Marcusson ( 2019 ). High impact on speaking/speech among the study participant may be due to the presence of cleft palate that restricts speech.…”
Section: Discussionmentioning
confidence: 95%
“…1,3 NOT-S ile şimdiye dek adenotonsiller hipertrofi, ektodermal displazi, Prader-Willi sendromu, Treacher Collins sendromu, serebral palsi, dudak ve damak yarığı, amyotrofik lateral skleroz, multipl skleroz, astım, temporomandibular bozukluk, oromandibular distoni ve Parkinson hastalığıyla ilişkili araştırmalar yapılmıştır. 5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Aynı zamanda Nordik dillerinde, Brezilya Portekizcesi, Fransızca dilinde geçerlilik ve güvenilirliği sağlanmıştır. 1,3,22 İngilizce ve farklı dillerdeki çevirisine ücretsiz olarak http://www.mun-h-center.se/en/information-material/not-s/ adresinden ulaşılabilmektedir.…”
unclassified
“…(15,4) 0 (0,0) TABLO 4: Olguların maloklüzyon açısından Nordik Orofasiyal Tarama Testinin toplam puanlarının dağılımı.…”
unclassified